Prophet of the restoration an exposition of the prophecy of Haggai - Tatford, Frederick Albert, 1901- (Sussex, UK Prophetic Witness, 1972)
Includes bibliographical references.
Brethren writer.
Keywords: Bible. O.T. Haggai -- commentaries